Globalization, economic freedom, and human rights - Dreher, Axel; Gassebner, Martin; Siemers, Lars (The journal of conflict resolution, 2012)
Using the KOF Index of Globalization and two indices of economic freedom, the authors empirically analyze whether globalization and economic liberalization affect governments’ respect for human rights in a panel of 106 countries over the 1981-2004 period. According to their results, physical integrity rights significantly and robustly increase with globalization and economic freedom, while empowerment rights are not robustly affected. Due to the lack of consensus about the appropriate level of empowerment rights as compared to the outright rejection of any violation of physical integrity rights, the global community is presumably less effective in promoting empowerment rights.